Clinicoepidemiological Profile and Short term Outcome of Abdominal Tuberculosis in Western Region of Bangladesh - Saha, Madhusudan; Islam, SAHM Mesbahul; Perveen, Irin; Aktar, Nasrin; Ahmed, Kabir; Hely, Musammat Aklima Akter; Zakaria, Mohammad; Hoque, Md Mazharul (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Introduction: Abdominal tuberculosis is not uncommon in daily medical practice. This study was done focusing variable presentations of abdominal tuberculosis Material and methods: Data of consecutive patients diagnosed as abdominal tuberculosis were analyzed. Their epidemiological features, presentations, laboratory findings, and response to therapy were analysed. Result: Total 69 cases (male 43, 62.3%,and female 26, 37.7%), age ranging from 15 to 85 years (mean 36.23) were enrolled. Rural (55, 79.7%), poor (49,71%) and housewives (24, 34.8%) and people of 21-30 years age group (27, 39.1%) were more affected. Diagnosis was based on combinations of clinical, laboratory findings and therapeutic response. In this series 30 (43.5%), 23 (33.4%) and 12 (17.3%) were diagnosed as intestinal, peritoneal and disseminated tuberculosis respectively. Of them68 patients recovered with treatment. Five patients developed intestinal obstruction and one developed hepatitis and lost from follow up. Conclusion: Diagnosis of abdominal tuberculosis is by combinations of clinical findings, without gold standard method. In our series intestinal tuberculosis and peritoneal tuberculosis were common clinical types with weight loss and abdominal pain as common clinical symptoms. And outcome of Treatment of TB was excellent J Bangladesh Coll Phys Surg 2019; 37(1): 25-29